2021
DOI: 10.1051/e3sconf/202125805014
|View full text |Cite
|
Sign up to set email alerts
|

Environmental protection policies at craft villages in Hanoi in the context of sustainable development

Abstract: Craft village is one of the distinct features of rural areas and an important factor in industrial and secondary manufacturing zones and subzones in Vietnam. Craft village, in nature, is a guild within a village who earn their living through non-agricultural activities. Craft village has been long preserved and developed with various characteristics including production subject (artisan); produce (featured by sophistication and arts); natural condition and specific technological process. In the context of indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…These programmes are very helpful because they give trainees direct access to the masters' vast knowledge and experience. Apprentices learn both technical skills and the intangible differences that make each craft practice unique through hands-on interaction and practical learning experiences (Nguyen et al, 2021). The programmes range from structured apprenticeships to more flexible mentorship arrangements.…”
Section: Master-apprentice Relationshipmentioning
confidence: 99%
“…These programmes are very helpful because they give trainees direct access to the masters' vast knowledge and experience. Apprentices learn both technical skills and the intangible differences that make each craft practice unique through hands-on interaction and practical learning experiences (Nguyen et al, 2021). The programmes range from structured apprenticeships to more flexible mentorship arrangements.…”
Section: Master-apprentice Relationshipmentioning
confidence: 99%
“…Mangrove forests in the South are also very rich and diverse: they cover tropical tidal coastal estuaries with an area of about 250,000 hectares; of which, Ca Mau province has the highest biological level in the country (32 main mangrove species and 32 other species of the same family) [39] and over 500 species of seaweeds. The southern coastal region has the Mekong River system that carries millions of tons of alluvium into the sea every year, with a tidal height of 2.5 -3.5 m. The area is warm and sunny all year round, with average temperature of 26°C and no winter season, facilitating the growth of mangroves [40].…”
Section: Marine Biological Resourcesmentioning
confidence: 99%
“…Then, Rong et al [24] pointed out that the restoration and reuse of architectural heritage can effectively preserve vernacular components and cultural narratives in the context of the sustainable development strategy of traditional architecture. Nguyen et al [25] indicated that architectural heritage can create core economic dynamics of the heritage site while shaping the subjectivity of the community, and the conservation of architectural heritage and the economic dynamics of the conservation site were studied in conjunction with the direction of the economic dynamics of the conservation site.…”
Section: Introductionmentioning
confidence: 99%